Ответы 1

  • 1) 0,4х +3 = (3х + 1) -х          0,4х +3 = 3х + 1 -х         3 -1 = 3х -х -0,4      2 = 1,6х        1,6х = 2      х = 2/1,6       х = 1,252) 3,4 -0,6х = 2х - (0,4х +1)      3,4 -0,6х = 2х -0,4х - 1      3,4 + 1 = 2х -0,4х +0,6х     4,4 = 2,2х         х = 2 
    • Автор:

      crane
    • 5 лет назад
    • 0
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years